1986
DOI: 10.1007/bf00455841
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in giant cell tumor of bone a modified histological grading system useful as a guide to prognosis

Abstract: An analysis of 26 patients with giant cell tumor of bone was carried out to determine the clinical and pathological factors affecting the prognosis of the tumor, with a follow-up program of more than 3 years. The physical characteristics of the pathological features were measured objectively using an image analyzer. A significant correlation between the therapeutic procedures and recurrence of the tumor was found, but no pathological variables were significantly correlated. Excision or resection en bloc should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…The number of giant cells was similar in primary and recurrent groups as seen previously. 4 Other features like stromal cell nucleoli score, giant cell nucleoli score, stromal cell groove score, and giant cell groove score were also not significantly different in primary and recurrent GCT.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The number of giant cells was similar in primary and recurrent groups as seen previously. 4 Other features like stromal cell nucleoli score, giant cell nucleoli score, stromal cell groove score, and giant cell groove score were also not significantly different in primary and recurrent GCT.…”
Section: Discussionmentioning
confidence: 89%
“…There is marked subjectivity in the histopathological grading systems and many reports on the correlation of histological features and prognosis have concluded that it is impossible to judge whether or not a GCT of bone is likely to recur from its histological characteristics. 4,15 At present, no grading system has proved to have prognostic relevance. Recent understanding of the cellular components of GCT and its molecular and cytokine-mediated derivation has shed new light on the nature of GCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations